2014
DOI: 10.3837/tiis.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A Signal Subspace Interference Alignment Scheme with Sum Rate Maximization and Altruistic-Egoistic Bayesian Gaming

Abstract: In this paper, we propose a distributed signal subspace interference alignment algorithm for single beam K − user (3 K ≥) MIMO interference channel based on sum rate maximization and game theory. A framework of game theory is provided to study relationship between interference signal subspace and altruistic-egoistic bayesian game cost function. We demonstrate that the asymptotic interference alignment under proposed scheme can be realized through a numerical algorithm using local channel state information at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We then compare the total achievable rate with same parameters configuration when the CRE offset 12 dB α = in Fig. 6, the minimum antennas number which satified the feasible condition of every proposed scheme is used as follows: case 1: (2, 2, 6, 3, 3, 1); case 2: (2, 3, 12, 4, 4, 1); case 3: (3,3,12,8,4,1). It is shown from each case that the total achievable rate of ODC-IA scheme is largest and that of ZF-IA is smallest.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then compare the total achievable rate with same parameters configuration when the CRE offset 12 dB α = in Fig. 6, the minimum antennas number which satified the feasible condition of every proposed scheme is used as follows: case 1: (2, 2, 6, 3, 3, 1); case 2: (2, 3, 12, 4, 4, 1); case 3: (3,3,12,8,4,1). It is shown from each case that the total achievable rate of ODC-IA scheme is largest and that of ZF-IA is smallest.…”
Section: Simulationsmentioning
confidence: 99%
“…IA is pioneered in multi-user multiple input multiple output (MU-MIMO) interference channel [5][6][7][8]. It concluded that each user can use half of the channel resources to make an interference-free communication regardless of user number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation